A review of the corrosion behavior of metallic heritage structures and artifacts - Darain, Kh Mahfuz ud; Jumaat, Mohd Zamin; Nazimuddin, S. M.; Ahsan, Amimul; Muhammad Rashid, Raizal Saifulnaz; A. Aziz, Md. Maniruzzaman; Obaydullah, M.; Saiful Islam, A. B. M. (Penerbit Universiti Teknologi Malaysia, 2015)
Awareness about restoring and preserving historically important structures and artifacts is gradually growing in many parts of the world. These artifacts and structures represent the culture, tradition and past of a nation. They are often also a source of national income through tourist activities. Besides masonry and wood work, metallic forms and relics are a vital part of the heritage which needs to be conserved. Certain metals have been used significantly throughout history in the creation of objects and structures. However, metals are prone to decay over time, particularly decay through corrosion. The basic mechanisms of metal corrosion, the various types of corrosion and existing remedial solutions are reviewed in this paper. The most significant factor affecting metal corrosion was found to be the surrounding environment, especially in marine areas. Different remedial measures can be implemented on corroded metals according to their specific properties. Recommendations for further study are offered at the end of the paper.